2019
DOI: 10.3389/fpls.2019.01515
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonate-Induced Defense Mechanisms in the Belowground Antagonistic Interaction Between Pythium arrhenomanes and Meloidogyne graminicola in Rice

Abstract: Next to their essential roles in plant growth and development, phytohormones play a central role in plant immunity against pathogens. In this study we studied the previously reported antagonism between the plant-pathogenic oomycete Pythium arrhenomanes and the root-knot nematode Meloidogyne graminicola, two root pathogens that co-occur in aerobic rice fields. In this manuscript, we investigated if the antagonism is related to imbalances in plant hormone levels, which could be involved in activation of plant de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…Transgenic lines deficient in OsCPS4 , a phytoalexin biosynthetic gene, showed increased susceptibility to rice blast fungus (Toyomasu et al, 2014). Also in nematodes it was shown that induction of DP biosynthesis increases resistance against nematodes (Verbeek et al, 2019). Some terpenoids might be involved in nematode resistance by accumulation in lesions near the infection site (Veech, 1982), so a reduced terpenoid content could influence susceptibility to nematodes.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic lines deficient in OsCPS4 , a phytoalexin biosynthetic gene, showed increased susceptibility to rice blast fungus (Toyomasu et al, 2014). Also in nematodes it was shown that induction of DP biosynthesis increases resistance against nematodes (Verbeek et al, 2019). Some terpenoids might be involved in nematode resistance by accumulation in lesions near the infection site (Veech, 1982), so a reduced terpenoid content could influence susceptibility to nematodes.…”
Section: Discussionmentioning
confidence: 99%
“…However, this hypothesis has evolved, suggesting diverse and more complicated mechanisms (e.g. physiological modifications, rhizosphere alternations) underlying these associations in different pathosystems (Back et al., 2002; Kyndt et al., 2017; Verbeek et al., 2019). Therefore, each plant‐fungus‐nematode association should be studied individually in order to assess the potential adverse effects on crops of interest, and estimate disease risk so as to develop effective management strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Even more recently, Verbeek et al. (2019) revealed that Meloidogyne graminicola suppresses jasmonic acid (JA) levels in rice roots to increase host susceptibility, whereas Pythium arrhenomanes boosts JA in a manner that prohibits JA repression by the nematode, leading finally to decreased RKN infestation in dual‐inoculated plants. However, several authors have speculated that nematode penetration is increased in plant roots previously subjected to fungal pathogens or that feeding sites of sedentary endoparasitic nematodes are preferred infection sites for plant pathogenic fungi (Back et al., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For example, among cereals, maize (Zea mays) produces both diterpenoid (kauralexins and dolabralexins) and sesquiterpenoid (zealexins) phytoalexins (Block et al, 2019), while rice produces three different classes of diterpenoid phytoalexins: momilactones, phytocassanes, and oryzalexins (Yamane, 2013). All these terpenoids are involved in defense against fungal, bacterial, and/or insect pests and pathogens (Dillon et al, 1997;Lu et al, 2018;Pichersky and Raguso, 2018;Block et al, 2019), and they are inducible by treatment with resistance inducers that reduce susceptibility to nematodes (Yamane, 2013;Verbeek et al, 2019); it may thus prove fruitful to investigate their role in PPN resistance.…”
Section: Terpenoidsmentioning
confidence: 99%